2015
DOI: 10.1097/sla.0000000000000688
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Hyperglycemia and Risk of Adverse Events Among Patients With and Without Diabetes

Abstract: Objective To study the association between diabetes status, perioperative hyperglycemia, and adverse events in a statewide surgical cohort. Background Perioperative hyperglycemia may increase the risk of adverse events more significantly in patients without diabetes (NDM) than in those with diabetes (DM). Methods Using data from the Surgical Care and Outcomes Assessment Program, a cohort study (2010–2012) evaluated diabetes status, perioperative hyperglycemia, and composite adverse events in abdominal, vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
277
3
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 357 publications
(302 citation statements)
references
References 29 publications
11
277
3
11
Order By: Relevance
“…In contrast, Kotagal et al 17. reported that the risk of complications was linked to hyperglycemia for non‐DM patients but not for DM patients, which is consistent with our results.…”
Section: Relationship Between Perioperative Bg and Ssi In Patients Whsupporting
confidence: 92%
See 4 more Smart Citations
“…In contrast, Kotagal et al 17. reported that the risk of complications was linked to hyperglycemia for non‐DM patients but not for DM patients, which is consistent with our results.…”
Section: Relationship Between Perioperative Bg and Ssi In Patients Whsupporting
confidence: 92%
“…There are currently several debates regarding the benefits of strict glucose control in less critically ill patients undergoing elective surgery as opposed to critically ill (medical) patients12, 13, 14, 15, 16, 17, 18 (Table 2). Although the recommended target BG is 140–180 mg/dL for most ICU patients,27 a recent meta‐analysis23 comparing the efficacy between an intensive and a conventional protocol in patients undergoing surgery showed a significant benefit for the intensive protocol in reducing SSI.…”
Section: Indication For Intensive Protocol In Critically Ill Patientsmentioning
confidence: 99%
See 3 more Smart Citations